The immunogenic potential of AZD1402 (Elarekibep) T-cell epitopes in healthy volunteers and drug-exposed clinical trial participants - Liam Farrell; Stephanie M Bates; Alexander Walker; Monday Ogese; Xiaoli Meng; Sian Piper; John Mo; Katy Saide; Jorrit Hornberg; David Close; Ian Wallace; Catherine J Betts; et al. (Archives of Toxicology, 2026)
AZD1402 (Elarekibep) is a novel anticalin with engineered IL-4Rα antagonist binding properties that was under development for inhaled treatment of asthma. Structural similarity to tear-lipocalin is thought to limit immunogenicity risk; however, a range of treatment-emergent hypersensitivity-like adverse events were observed in a clinical study. This study aimed to (i) explore the activation of drug-exposed human T-cells with AZD1402- and tear lipocalin-derived peptides, (ii) characterise any T-cell epitopes contained within AZD1402 and (iii) define the nature of any response. Peripheral blood mononuclear cells (PBMC) from AZD1402-exposed study participants, alongside AZD1402-naïve donors, were cultured with AZD1402 and AZD1402-derived overlapping 18mer peptides. Proliferation and cytokine secretion were measured. T-cell clones were generated to characterise the diversity of T-cell epitopes and reactivity against equivalent tear-lipocalin peptides. AZD1402 contained multiple epitopes located in engineered “hotspot” regions of the molecule that activated PBMC and MHC class II-restricted CD4 + T-cell clones from both study participants and AZD1402-naïve donors. T-cell stimulatory peptides contained amino acid substitutions generated through mutagenesis to create AZD1402 target binding properties; similar T-cell epitopes were not found in tear-lipocalin. Detection of T-cell clones responsive towards AZD1402 and AZD1402-derived peptides provides evidence that immunogenic epitopes are formed naturally through processing of the AZD1402. These data describe a recall immunogenicity risk associated with AZD1402 and provide a framework by which to explore the immunogenic potential of modified sequences within anticalin or other large molecule therapeutics.

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

A reproductive and trophic analysis of corals in a degraded environment - Morgan L. Short; Hilary G. Close; David S. Gilliam; Joana Figueiredo (Coral Reefs, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An assessment of ectomycorrhizal fungal communities in Tasmanian temperate high-altitude Eucalyptus delegatensis forest reveals a dominance of the Cortinariaceae - Bryony M. Horton; Morag Glen; Neil J. Davidson; David A. Ratkowsky; Dugald C. Close; Tim J. Wardlaw; Caroline Mohammed (Mycorrhiza, 2017)

Population genomics of P acific lamprey: adaptive variation in a highly dispersive species - Jon E. Hess; Nathan R. Campbell; David A. Close; Margaret F. Docker; Shawn R. Narum (Molecular Ecology, 2013)
Unlike most anadromous fishes that have evolved strict homing behaviour, P acific lamprey ( E ntosphenus tridentatus ) seem to lack philopatry as evidenced by minimal population structure across the species range. Yet unexplained findings of within‐region population genetic heterogeneity coupled with the morphological and behavioural diversity described for the species suggest that adaptive genetic variation underlying fitness traits may be responsible. We employed restriction site–associated DNA sequencing to genotype 4439 quality filtered single nucleotide polymorphism ( SNP ) loci for 518 individuals collected across a broad geographical area including B ritish C olumbia, W ashington, O regon and C alifornia. A subset of putatively neutral markers ( N = 4068) identified a significant amount of variation among three broad populations: northern B ritish C olumbia, C olumbia R iver/southern coast and ‘dwarf’ adults ( F CT = 0.02, P ≪ 0.001). Additionally, 162 SNP s were identified as adaptive through outlier tests, and inclusion of these markers revealed a signal of adaptive variation related to geography and life history. The majority of the 162 adaptive SNP s were not independent and formed four groups of linked loci. Analyses with matsam software found that 42 of these outlier SNP s were significantly associated with geography, run timing and dwarf life history, and 27 of these 42 SNP s aligned with known genes or highly conserved genomic regions using the genome browser available for sea lamprey. This study provides both neutral and adaptive context for observed genetic divergence among collections and thus reconciles previous findings of population genetic heterogeneity within a species that displays extensive gene flow.

Molecular cloning, characterization, and gene expression of the androgen receptor in the large yellow croaker, Larimichthys crocea - Lulu Pu; Kunhuang Han; Fangjing Xie; Zhihua Zou; David Close; Ziping Zhang; Yilei Wang (Fish Physiology and Biochemistry, 2013)

Exploiting regulatory variation to identify genes underlying quantitative resistance to the wheat stem rust pathogen Puccinia graminis f. sp. tritici in barley - Arnis Druka; Elena Potokina; Zewei Luo; Nicola Bonar; Ilze Druka; Ling Zhang; David F. Marshall; Brian J. Steffenson; Timothy J. Close; Roger P. Wise; Andris Kleinhofs; Robert W. Williams; et al. (Theoretical and Applied Genetics, 2008)

An atlas of gene expression from seed to seed through barley development - Arnis Druka; Gary Muehlbauer; Ilze Druka; Rico Caldo; Ute Baumann; Nils Rostoks; Andreas Schreiber; Roger Wise; Timothy Close; Andris Kleinhofs; Andreas Graner; Alan Schulman; et al. (Functional & Integrative Genomics, 2006)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Multifaceted genetic analysis of the “Critically Endangered” brush-tailed rock-wallaby Petrogale penicillata in Victoria, Australia: Implications for management - Teena L. Browning; David A. Taggart; Catherine Rummery; Robert L. Close; Mark D.B. Eldridge* (Conservation Genetics, 2001)

Delineation of a landfill leachate plume and flow channels in coastal sands near Christchurch, New Zealand, using a shallow electromagnetic survey method - David C. Nobes; Mark J. Armstrong; Murray E. Close (Hydrogeology Journal, 2000)